Cegah Osteoporosis Lansia: Nutrisi Sehat Dan Latihan Aktivitas Tepat Untuk Tulang Kuat Di Posyandu Lansia Wijaya Kusuma Ketelan - setiyanto, Riyan; Setyorini, Wahyu; Aisyah, Siti Nur; Noviani, Wulan Suci (Politeknik Indonusa Surakarta, 2025)
Osteoporosis is one of the major health problems in the elderly that can reduce the quality of life due to the increased risk of fractures. This community service activity aims to increase awareness and knowledge of the elderly about osteoporosis prevention, reduce the risk of fractures and osteoporosis complications, encourage positive behavioral changes in optimizing a balanced diet and safe, targeted and appropriate physical activity and improve the quality of life of the elderly. Early prevention efforts are very important, especially through the right nutritional approach and physical activity. Educational activities at the Wijaya Kusuma Elderly Posyandu, Ketelan Village, are expected to increase awareness and knowledge of the elderly about the importance of calcium and vitamin D-rich nutrition, as well as appropriate physical exercise to strengthen bones. Through counseling and simulation of healthy bone gymnastics, the elderly are encouraged to implement a balanced diet and routinely do light exercise such as walking, elderly gymnastics, and stretching. The results of the activity showed an increase in participants' understanding of how to prevent osteoporosis and their commitment to changing their lifestyle. This program is expected to be the first step in reducing the incidence of osteoporosis among the elderly in a sustainable manner. Keywords: educational; elderly; Osteoporosis